Comparison of Minimally Invasive Tissue Sampling With Conventional Autopsy to Detect Pulmonary Pathology Among Respiratory Deaths in a Resource-Limited Setting. Issue 1 (22nd April 2019) - Roberts, Drucilla J; Njuguna, Henry N; Fields, Barry; Fligner, Corinne L; Zaki, Sherif R; Keating, M Kelly; Rogena, Emily; Walong, Edwin; Gachii, Andrew K; Maleche-Obimbo, Elizabeth; Irimu, Grace; Mathaiya, John; et al.
Abstract: Objectives: We compared minimally invasive tissue sampling (MITS) with conventional autopsy (CA) in detection of respiratory pathology/pathogens among Kenyan children younger than 5 years who were hospitalized with respiratory disease and died during hospitalization. Methods: Pulmonary MITS guided by anatomic landmarks was followed by CA. Lung tissues were triaged for histology and molecular testing using TaqMan Array Cards (TACs). MITS and CA results were compared for adequacy and concordance. Results: Adequate pulmonary tissue was obtained by MITS from 54 (84%) of 64 respiratory deaths. Comparing MITS to CA, full histologic diagnostic concordance was present in 23 (36%) cases and partial concordance in 19 (30%), an overall 66% concordance rate. Pathogen detection using TACs had full concordance in 27 (42%) and partial concordance in 24 (38%) cases investigated, an overall 80% concordance rate. Conclusions: MITS is a viable alternative to CA in respiratory deaths in resource-limited settings, especially if combined with ancillary tests to optimize diagnostic accuracy.